Pengaruh Kualitas Produk dan Harga Terhadap Keputusan Pembelian Pada Produk UMKM Dekranasda Kota Depok - Citradewi, Jihan; Siska, Elmira; Indra, Natal (Universitas 17 Agustus 1945 Semarang, 2025)
This study aims to determine the influence of product quality and price on purchasing decisions for MSME products in Dekranasda Depok City. The method used in this study is a quantitative approach with primary data collection through questionnaires. The sample in this study consisted of 50 consumers who shopped at Dekranasda Depok City and were selected using the side-by-side accidental method. Data analysis was performed using descriptive statistics, instrument data tests, multiple regression analysis, and hypothesis testing using IBM SPSS Statistics 25 software. The results showed that product quality partially impacts purchasing decisions, and prices partially impact MSME product purchasing decisions. When these two variables are observed simultaneously, both product quality and price have a significant influence on the purchase decision of MSME products Dekranasda Depok City